1993
DOI: 10.1073/pnas.90.12.5391
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of opiates, opioid peptides, and opioid receptors.

Abstract: Presently she cast a drug into the wine of which they drank to lull all pain and anger and bring forgetfulness of every sorrow." The Odyssey, Homer (Ninth century B.C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
244
0
10

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(263 citation statements)
references
References 21 publications
(7 reference statements)
1
244
0
10
Order By: Relevance
“…These drugs opened the way to the discovery of the endogenous opioid system in the brain. 43 The term "opioids" includes "opiates" as well as semisynthetic and synthetic compounds (e.g. heroin and morphine) with similar properties.…”
Section: ) Opioidsmentioning
confidence: 99%
“…These drugs opened the way to the discovery of the endogenous opioid system in the brain. 43 The term "opioids" includes "opiates" as well as semisynthetic and synthetic compounds (e.g. heroin and morphine) with similar properties.…”
Section: ) Opioidsmentioning
confidence: 99%
“…For example, a recent study of the opioid analgesic, tramadol, showed that slowing the rate of dose titration reduced the rate of adverse effect-related study withdrawal. 27 Regarding fear of addiction, the historical association of opioids with centuries of illicit misuse 28 may cause patients, in the most extreme sense, to relate longterm opioid therapy with the stigma of becoming a heroin addict. However, it is critical to note that opioid treatment of pain rarely results in addiction.…”
Section: Pain Treatment Features and Patient Attitudesmentioning
confidence: 99%
“…The endogenous ligands include more than 20 opioid peptides derived from three precursors: proenkephalin (PENK), prodynorphin (PDYN) and proopiomelanocortin (POMC) (Brownstein, 1993). In several studies components of the opioid system from human placental tissue have been isolated (Sastry et al, 1980;Liotta et al, 1982;Ahmed et al, 1986;Belisle et al, 1988), but the physiological role of the opioid receptors and peptides in the placenta, an organ lacking innervation, is not fully understood yet.…”
Section: Genes Previously Described In the Context Of Reproductive Prmentioning
confidence: 99%